Epidemiological Survey and Confirmation of Autochthonous Cases of Bovine Fasciolosis in the Serrana Mesoregion of Santa Catarina, Brazil - Américo, Larissa; Padilha, Mayckon Antonio Cardoso; Arruda, Paula Maciel; Drescher, Guilherme; de Moura, Anderson Barbosa; Chryssafidis, Andreas Lazaros (Frontiers in Veterinary Science, 2022)
Fasciola hepatica is reported as a trematode of great importance, causing fasciolosis, one of the most neglected zoonotic parasitic diseases in the world. In Brazil, potential losses of around US$ 210 million per year were calculated, with bovine fasciolosis alone. The State of Santa Catarina is located in the South Region of Brazil, with a herd of more than 4 million ruminants. The Serrana Mesoregion, historically free of fasciolosis, is composed of 30 municipalities, which have a consolidated agricultural tradition, mainly in extensive ruminant livestock. The objective of the present work was to investigate the occurrence and distribution of autochthonous cases of bovine fasciolosis in the region. For this, different analyzes were carried out in rural properties from eight municipalities, and in three slaughterhouses under the State Inspection Service (SIE), which received animals from all the Serrana Mesoregion. The rural properties were randomly selected, and up to 20 fecal samples were collected from random cattle older than one year, for analysis by coproparasitological sedimentation test. The traceability records of the positives were checked, for identifying autochthonous cases. Additionally, the tracking data of cattle slaughtered between the years of 2018 and 2021, which presented liver condemnations, were analyzed for defining autochthonous cases of bovine fasciolosis. In total, there were fecal samplings in 106 farms, with 1,927 tested cattle. From these, 178 (9.2%) were positive and autochthonous, but the overall result did not reflect the heterogeneity found between the evaluated municipalities. During the analyzed period, 11,556 cattle were slaughtered, with 1744 (15.1%) liver condemnations due to fasciolosis in animals that never left the Serrana Mesoregion. The present study confirmed the presence of autochthonous cases of bovine fasciolosis in municipalities of the Serrana Mesoregion, and verified a high rate of positivity in animals slaughtered in the regional slaughterhouses. When the prevalence of bovine fasciolosis in vivo was compared with the postmortem positivity index in five municipalities, the results disagreed in four municipalities (p-value <0.05), emphasizing the need for field investigation for the better understanding of the distribution and frequency of the parasitosis.